2017
DOI: 10.1016/j.jogn.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Gestational Weight Gain in a Population-Based Sample of Perinatal Women

Abstract: Objective To examine the effects of intimate partner violence (IPV) at varied time points in the perinatal period on inadequate and excessive gestational weight gain. Design Retrospective cohort using population-based secondary data. Setting Pregnancy Risk Assessment Monitoring System and birth certificate data, including New York City and 35 states. Participants Data were obtained for 251,342 U.S. mothers who gave birth from 2004–2011 and completed the Pregnancy Risk Assessment Monitoring System survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Once duplicates had been eliminated and titles and abstracts had been screened, 127 potentially relevant studies were selected and read in full. Ultimately, 50 studies ( n = 33 190 558 women) were included (Figure ). A summary of the results shown is presented in Table S1, which includes the characteristics of the population and studies, the types and proportion of population in the study reporting IPV, perinatal health outcomes reported and the quantification of the strength of association with different types of outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Once duplicates had been eliminated and titles and abstracts had been screened, 127 potentially relevant studies were selected and read in full. Ultimately, 50 studies ( n = 33 190 558 women) were included (Figure ). A summary of the results shown is presented in Table S1, which includes the characteristics of the population and studies, the types and proportion of population in the study reporting IPV, perinatal health outcomes reported and the quantification of the strength of association with different types of outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Forty‐one studies (82%, n = 41) were of high methodological quality (indicating low risk of bias) (Table ) . Most of the studies with high or moderate risk of bias obtained low scores in sample selection or comparability …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations